2012
DOI: 10.1155/2012/320698
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Weighted Support Vector Machine Based on Particle Swarm Optimization for Gene Selection and Tumor Classification

Abstract: We develop a detection model based on support vector machines (SVMs) and particle swarm optimization (PSO) for gene selection and tumor classification problems. The proposed model consists of two stages: first, the well-known minimum redundancy-maximum relevance (mRMR) method is applied to preselect genes that have the highest relevance with the target class and are maximally dissimilar to each other. Then, PSO is proposed to form a novel weighted SVM (WSVM) to classify samples. In this WSVM, PSO not only disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
(24 reference statements)
0
30
0
Order By: Relevance
“…Available kernels for support vector machines include linear, polynomial, sigmoid and radial basis functions (Meyer, 2017[96]). Some studies have acquired that radial basis function (RBF) provide higher accuracy to other kernel functions particularly in nonlinearly separable training data (Abdi et al, 2012[3]; Anand et al, 2010[9]).…”
Section: Cornerstones Of a Cad Systemmentioning
confidence: 99%
“…Available kernels for support vector machines include linear, polynomial, sigmoid and radial basis functions (Meyer, 2017[96]). Some studies have acquired that radial basis function (RBF) provide higher accuracy to other kernel functions particularly in nonlinearly separable training data (Abdi et al, 2012[3]; Anand et al, 2010[9]).…”
Section: Cornerstones Of a Cad Systemmentioning
confidence: 99%
“…The PSO algorithm was developed for the optimization of functions that are not continuously linear. The support vector machine used in the study was optimized by the particle swarm algorithm [44][45][46].…”
Section: Classification Phasementioning
confidence: 99%
“…Radial basis function (RBF) kernels are one of the most used kernels to separate data in SVM classifiers in complex classification environments. Some previous works have found that RBF kernel generally provides better classification accuracy than many other kernel functions [14]. This kernel nonlinearly maps samples into a higher-dimensional space.…”
Section: Kernel Selection and Parameters Tuningmentioning
confidence: 99%